Pandemic as a Challenge for Teaching Art in the Lower Grades of Elementary School in the Republic of Serbia - Мarija M. Pavlović; Аna D. Sarvanović (University of Belgrade, Teacher Education Faculty, 2022)
n the introductory part of the paper, based on the relevant and professional literature in the domain of art, the authors look at the significance of visual arts for the entire development and goodquality education of children. The total numer of lessons assigned for the school subject Art in the curricula for grades one to four of elementary education in Serbia is taken into consideration in order to point to the status of this subject in the lower grades of elementary school. The pandemics caused by the virus SARS-CoV-2 began in 2020 and it is still present in the world. It has redefined our way of living and made teachers look for new forms of organizing their lessons in line with the epidemiological measures. The aim of this paper is to investigate, in the context of Art instruction, how elementary school teachers have coped with the challenges created by the pandemic and determine whether this teaching area has changed its status relative to other teaching areas. The respondents to our questionnaire were 138 (N=138) elementary school teachers from different Serbian towns. The obtained results indicate that these teachers had to modify and adapt their teaching to a considerable extent. The conclusion is that elementary school teachers stress out the negative effects of the changes - a reduced number of Art lessons, shorter duration of lessons, the impossibility of pair and group work, as well as the introduction of online lessons - on the development of children's art creativity.